Miss julia delivers the goods eaudiobook Miss julia series, book 10. - Ross, Ann B. (Miss Julia, 2009)
In this delightful tale by New York Times best-selling author Ann B. Ross, America's favorite senior citizen determines to reunite two troubled souls before it's too late. Miss Julia reckons Mr. J.D. Pickens is the key to solving all of Hazel Marie's problems, especially the female kind. But how can Miss Julia coax the savvy PI back to town-and back into the arms of her 40-something friend Hazel Marie?